Analysis of Regional Economic Growth Disparities in Nusa Tenggara Barat Using The Heterogeneous Coefficient Spatial Durbin Panel Model: Analysis of Regional Economic Growth Disparities in West Nusa Tenggara Province Using the Heterogeneous Coefficient Spatial Durbin Panel Model - mawaddah juliarti; Siti Hariati Hastuti; Alissa Chintyana (Jurnal Forum Analisis Statistik, 2026)
Disparities in economic growth between regions in West Nusa Tenggara Province still pose a fundamental problem in achieving fair and equitable development. This study aims to analyze the factors influencing regional economic growth and identify spatial disparities and structural variations between districts/cities. The method used was the Heterogeneous Coefficient Spatial Panel Model (HCSPM) with the Heterogeneous Coefficient Spatial Durbin Model (HSDM) approach, which allows regression coefficients to vary across regions and considers spatial effects both directly and indirectly. The data used was annual panel data from 10 districts/cities in NTB over the period 2018-2024, with variables including the number of BTS towers, population size, percentage of poor population, investment, average years of schooling, and human development index. The analysis results indicate significant heterogenity acress regions and a strong spatial effect (p = 0.899), with R² reaching 0.998. Some regions show a negative influence from local variables but benefit positively from spillover effect from neighboring regions. Based on these findings, economic development policies in NTB are recommended to be region based, taking into account local characteristics and potential cross regional effects, particularly in infrastructure development and human resource improvement. Keywords: Heterogeneous Spatial Durbin Models (HSDM), Economic Inequality, West Nusa Tenggara (NTB), PDRB Capita.